Case report: Thoracolumbar spinal stenosis associated with alkaptonuria - Ding, Hong; Wang, Liang; Feng, Gan-Jun; Song, Yue-Ming; Liu, Li-Min (Frontiers in Surgery, 2023)
Background: Alkaptonuria is a rare autosomal genetic disorder. Spinal invasion is often manifested in the later stages of the disease. However, the presentation of thoracolumbar spinal stenosis is the first report. Case presentation: We report a case of a 61-year-old female patient with significant thoracolumbar stenosis symptoms. The patient had obvious kyphosis with preoperative lower extremity muscle strength grade 2. Signs and radiological findings are similar to those of ankylosing spondylitis. However, we found that the patient had melanin deposits on the sclera and skin, and the urine was darkened at rest. Imaging suggested no bone bridge connection between vertebrae. Patient underwent spinal decompression and vertebral body fixation. Urine specimen testing and intraoperative pathology indicated alkaptonuria. Post-operative recovery was good, the patient had significantly relieved pain and could stand and walk. Conclusion: This case is the first report of thoracolumbar spinal stenosis associated with alkaptonuria invasion of the spine. We reviewed the natural history, clinical differential diagnosis and treatment of alkaptonuria.